ALPHA-RECOIL IN U-PB GEOCHRONOLOGY: EFFECTIVE SAMPLE SIZE MATTERS - Romer R.L. (My University, 2003)
Displacement of the daughter isotope by a-recoil results in an open system on the nanoscale. For a heterogeneous distribution of U and Th, this redistribution of intermediate and stable daughter isotopes results in subvolumes with a deficit of Pb and others with an excess of Pb. Whether such heterogeneities affect the analyzed U–Pb system depends on: (1) the volume of the analyzed sample, (2) the degree and scale of heterogeneity in the U and Th distribution, and (3) the analytical procedure. Spatial separation of parent and daughter through a-recoil affects the U–Pb systematics of leached samples, where leaching gives access to domains less than 1m wide. Anomalous data patterns originating from recoil induced parent-to-daughter fractionation are more important if there are strong heterogeneities in the U and Th distribution, whereby Pb excess appears more pronounced than Pb deficit. Fractionation of parent and daughter elements through selective dissolution of U-REE-rich growth zones in zircon and U-inclusions in columbite, as well as the presence of U–Th-rich micro-inclusions in silicates dated using a step-leaching scheme, may result in anomalous 207Pb rad/ 206Pb rad, scattered 206Pb rad/ 238U and 207Pb rad/ 235U, and reverse discordance. The accumulated structural damage controls the leaching and dissolution behavior, but may also influence the non-stoichiometric element mobilization during sputtering or ablation in the analysis of U-rich samples by SHRIMP and LA-MC-ICP-MS.